Face the Inevitable, Embrace Parallelism. (Communications of the ACM, 2009)
The article gives the author's viewpoint that hardware engineers and software developers should recognize trends toward parallel programming and design their computer applications accordingly. The author discusses software abstraction, Moore's Law concerning transistor power and the acceleration of processing requirements, and the experience of the end user.